Catastrophic floods in Kosi catchment during August 2008 (MAUSAM, 2011)
A breach in embankment of Kosi barrage was reported on 18 August, 2008 which has changed its course and resulted in a fresh channel around 120 km to the east of its previous channel. At the time of failure of the embankment, gushing out of about 2832 m3/s water with great impact breaking into the Mahendra Rajmarg and then taking a southward route into the old 1892-1921 abandoned course of the river, thus leaving the pre-breach C-loop and following a straight route to the Ganga. In this study meteorological aspect are analysed in details in relation to the catastrophic flood in the Kosi river catchment during August 2008. It seems that this catastrophic flood may not be solely due to rainfall in the catchment of Kosi. The breach is due to incorrect strategies of river management, human negligence and poor maintenance of afflux bund of the barrage (Sinha, 2009).